(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This article outlines the radical transformation of educational policies in Russia since 2020, displaying the timing of the individual stages of the rooting of state propaganda in schools, the militarization of school education, and the spread of neo-nationalist ideology among schoolchildren aged 6 to 19. This paper aims to raise awareness of the extreme instrumentalization of historical narratives for state propaganda goals in national education. It also intends to illustrate the extent of the militarization of education and the destructive nature of any propaganda during one’s upbringing. Emphasis will be given to the actions made by the Russian government to develop the whole complex of state-build patriotism, which is about militarization, neo-nationalistic propaganda and rewritten history.